Prevalence of Dehydration and The Relationship with Fluid Intake and Self-Assessment of Hydration Status in Czech First League Soccer Players - Klimesova, Iva; Krejci, Jakub; Botek, Michal; McKune, Andrew J; Jakubec, Ales; Neuls, Filip; Sladeckova, Barbora; Valenta, Michal (Journal of human kinetics, 2022)
The objective of this cross-sectional study was to evaluate the hydration status of Czech First League soccer players, and to compare the reported fluid intake, perceived fluid intake and thirst sensation of euhydrated (EU) and dehydrated (DE) players. The study involved 124 Czech male professional soccer players (age 25.2±5.0 years) participating in annual winter, pre-season laboratory testing. Hydration status was assessed based on urine specific gravity (USG), euhydration was set at USG≤1.020. Fluid intake and thirst perception were evaluated by a questionnaire. The sample mean for USG was 1.021±0.008, 56% of players were dehydrated. Reported daily fluid intake was significantly (p<0.001, d=0.95, large effect) higher in EU compared to DE players. Daily fluid intake negatively correlated with USG (rS=-0.46, p<0.001, medium effect). The fluid intake perception score was significantly (p=0.005, d=0.54, medium effect) better in EU compared to DE players. Reported intake perception scores negatively correlated with USG (rS=-0.32, p<0.001, medium effect). However, there was no correlation (rS=-0.09, p=0.34, trivial effect) between thirst perception scores and USG. Thirst perception scores were not significantly different between EU and DE players (p=0.35, d=0.18, trivial effect). Our results indicated that self-assessment of both daily fluid intake and perceived fluid intake matched with objective hydration status, while self-assessment of thirst perception was not an appropriate indicator of hydration status in elite soccer players.
Keywords: self-assessment questionnaire; athletes; dehydration; urine specific gravity